A Review on Adaptive Strategies for Climate Resilience in Agricultural Extension Services in India - Rajesh C M; Abhishek Jadhav; Manohar K N; Prahlad P Bhat; Rahul Prasad R; Anil K; Pavan V (Archives of Current Research International, 2024)
Adaptive strategies for enhancing climate resilience in agricultural extension services in India, amidst escalating climate challenges. It begins by delineating the profound impacts of altered weather patterns, increased frequency of extreme weather events, and shifting pest and disease dynamics on agricultural practices. The paper then delves into the variety of technological innovations, management practices, and policy interventions currently being implemented to bolster climate resilience. Notably, it highlights the adoption of precision agriculture technologies, climate-smart agricultural tools, and the innovative use of ICT in extension services to provide timely, targeted advice to farmers. On the management front, the paper discusses the significant benefits of crop diversification, advanced water management strategies like rainwater harvesting and drip irrigation, and improved soil health practices, which collectively contribute to a sustainable and resilient agricultural system. Policy and institutional adaptations are also examined, emphasizing the crucial role of supportive policy frameworks, community engagement, and multi-stakeholder partnerships in scaling successful adaptations and ensuring their sustainability. Drawing on international case studies-from Vietnam’s effective water management techniques to Zambia’s success with crop diversification and the technological advancements in North American agriculture-the review identifies key factors contributing to their success, challenges faced, and the potential for transferring these strategies to the Indian context. Each case study provides insights into overcoming barriers to adoption and highlights the importance of integrating local and scientific knowledge to achieve long-term sustainability. Concludes by stressing the need for a multi-faceted, inclusive approach that aligns with local environmental, cultural, and economic contexts to effectively address the unique challenges posed by climate change to Indian agriculture.